Nutritional intervention in end-stage renal disease: a clinical trial study - Tao, Xueting; Qian, Jiaolin; Hu, Yongwei (Frontiers in Nutrition, 2024)
Objective Chronic kidney disease is a global health problem, and end-stage renal disease (ESRD) has a major impact on patients' quality of life and prognoses. However, studies on individualized nutritional therapy for patients with ESRD need more complementary evidence. Methods A clinical study was conducted based on a small population. It included patients with ESRD who underwent dialysis treatment in the Taicang Hospital Department of Nephrology, Soochow University, China, between January 2019 and December 2021. According to the randomized number table method, patients were divided into the nutritional treatment group (NIG) and the non-nutritional intervention control group (NNIG). There were 84 patients in the NIG and 92 patients in the NNIG. This study analyzed the changes in residual renal function (RRF) and indicators of blood and kidney function in ESRD with personalized nutritional therapy. Results The results show that nutritional interventions for ESRD are effective in reducing the rate of decline in RRF and improving indicators of blood and kidney function in patients with ESRD. It was also found that patients with diabetes mellitus gained fewer health benefits per unit of RRF improvement with individualized nutritional therapy. Conclusion This study provides important information about the treatment effects and factors associated with individual nutritional interventions in a population with ESRD. These results contribute to a better understanding of the effects of nutritional therapy in ESRD and provide a basis for managing it. Further studies should focus on specific populations and potential interventions to improve patient prognosis.